A Study of Some Relationships between Accounting and Decision-Making Processes. - Culpepper, Robert C. (The Accounting Review, 1970)
Abstract Accounting information influences many decisions, but little is known about the way in which this influence is exerted in particular classes of decisions. If the facilitation of decisions is taken as the purpose of accounting, then accounting measurement methods ought to be evaluated in terms of their influence on the decision-making process. The article looks at permitted rates of return for privately owned natural gas distribution utilities. It attempts to relate differences in these rates of return with differences in accounting methods used. It is observed that as compared to many other decisions, the regulatory decision is fairly well standardized. In addition, the output of the decision is a single unambiguous number. For these reasons the regulatory decision is studied with expectations of a greater probability of obtaining meaningful results than would be the case with well-structured decisions. Finally, whether decision-makers are influenced in their decisions because of fixation or because of their choice of a particular method of measuring an accounting variable, the fact that decisions may be influenced by the related accounting process points to a need for greater research efforts directed at finding objective criteria for selection among alternative accounting methods for particular purposes.